Exploring the Needs and Perceptions of Women of Reproductive Age Toward a Digital System for Early Breast Cancer Detection: A Qualitative Study - Novita Nining Anggraini; Juwita Muspita Sari (Journal of Public Health Indonesian, 2026)
Breast cancer is the most common malignancy among women worldwide, and early detection remains the most effective strategy for reducing mortality. Digital technologies, including artificial intelligence and mobile applications, are increasingly proposed to support early detection, yet perspectives of women of childbearing age toward such systems remain poorly understood. Objective: This study explored the needs and perceptions of women of childbearing age (15–49 years) regarding a digital breast cancer early detection system. A qualitative descriptive design was used. Twenty participants were purposively selected and engaged through in-depth interviews and two focus group discussions. Data were analyzed using Braun and Clarke's thematic analysis, and trustworthiness followed Lincoln and Guba's criteria. Four themes emerged: perceived benefits of digital early detection, perceived barriers and concerns, contextual needs for adoption, and preference for a human technology hybrid model of care. Participants valued convenience, privacy, and empowerment but expressed concerns regarding digital literacy, trust in algorithmic accuracy, cost, and data security. Women of childbearing age hold generally positive yet conditional perceptions toward digital breast cancer early detection systems. Successful implementation requires digital literacy support, transparent communication about accuracy and privacy, affordability, and integration with trusted human healthcare providers